Antibacterial effect of a toothpaste with xylitol on Streptococcus mutans in pregnant women's saliva - Roxana Patricia Escalante-Medina; Angel Steven Asmat-Abanto; Miguel Angel Ruiz-Barrueto (Editorial Ciencias Médicas, 2019)
Introduction: Some physiological changes occur in women during pregnancy which cause an increase in dental plaque and cariogenic microbiota. This situation, alongside a modification in the diet and inadequate oral hygiene, negatively affect the oral health of both the mother and the baby. Objective: Determine the antibacterial effect of a toothpaste with xylitol on the count of Streptococcus mutans in pregnant women's saliva. Methods: A double-blind clinical trial was conducted in José Olaya Health Center (Chiclayo, Peru) in January 2017. The sample population was 50 women in the second trimester of pregnancy who met the established inclusion criteria. Two groups were formed: 25 pregnant women used a toothpaste with 10% xylitol and the other 25 used a toothpaste without xylitol. A saliva sample was taken and processed microbiologically before the start of the study and 14 days after use of the two toothpastes. A count was performed of colony-forming units for Streptococcus mutans in saliva with highly significant reliability, using the intraclass correlation coefficient, and intra- and inter-rater calibration (1.000 and 0.999, respectively). Data analysis was based on the Mann-Whitney U Test, with a significance level of 5%. Results: No significant difference was found between the pregnant women who used the toothpaste with xylitol and those who used the toothpaste without xylitol (p= 0.062). Conclusions: The antibacterial effect of the commercial toothpaste with xylitol is similar to that of a toothpaste without xylitol in terms of the Streptococcus mutans count in pregnant women's saliva.